Posterior vertebral column resection for correction of thoracolumbar kyphosis after failed anterior instrumented fusion. Issue 29 (17th July 2020) - Lu, Jian; Dai, Zhe-Hao; Li, Hai-Sheng; Kang, Yi-Jun; Chen, Fei
Abstract : Abstract: To explore the effectiveness of posterior vertebral column resection for failed thoracolumbar anterior instrumented fusion. Ten patients with anterior fusion with refractory pain, progressive neurological deficits, and kyphosis were recruited. Anterior removal of the implant and posterior vertebral column resection were performed. The mean operating time, intraoperative blood loss, kyphosis angle, visual analog scale pain score, Oswestry disability index, bone fusion time, and complications were assessed in a minimum 18-month follow-up. The mean operating time was 323.5 ± 63.6 minutes, with a mean blood loss of 1189 ± 253.4 mL. The mean preoperative kyphosis angle of 54.6° ± 8.0° immediately decreased to 4.8° ± 1.5° after revision surgery and eventually to 6.8° ± 1.3° at the final follow-up. The mean bone fusion time was 6.8 ± 1.2 months. All patients had satisfactory sagittal and coronal balance with no implant failure at the last follow-up. The average visual analog scale score was 6.2 ± 1.0 preoperatively, and it decreased to 2.6 ± 0.5 at the last follow-up. No patient suffered from neurological deterioration. The Oswestry disability index decreased from 39.8% ± 4.6% preoperatively to 24.5% ± 4.7% at the final follow-up. Complications occurred in 4 patients: 3 experienced tearing of the lung, and 1 had a superficial wound infection. Anterior removal of the implant and posterior vertebral column resection constituted a safe and effective revision surgery for patients with prior anterior fusion with rigid postsurgical deformities.